Examining the differences in assessing quality of translations and acceptability of texts - Burazer, Lara (ELOPE (Ljubljana), 2013)
The main focus of modern Translation Studies seems to be the ever changing challenges of successful cross-cultural communication. With globalisation of society, limitations in mutual understanding are surfacing, which are usually followed by the communicator's failure to meet the other party's expectations. Such expectations are not only linguistically, but culturally embedded and might prove difficult to grasp for those who are not closely connected to the particular culture. Mastering linguistic abilities is an inevitable requirement and represents an important aspect of cross-cultural communication, but achieving a high level of acceptability of (translated) texts proves to be just as important, while not always directly related to the traditional linguistic aspects of the text. It requires meeting the expectations of the target audience which exceed the scope of grammar and vocabulary. Prior cultural and discoursal experience with relevant texts proves to play an important role in producing translations which meet the target audience's expectations in terms of linguistic, but more importantly in terms of discoursal characteristics.
Keywords: kakovost prevoda; prevajanje; pričakovanja; sprejemljivost besedila; translation